An update on the clinical trial research of immunotherapy for glioblastoma - Zhou, Yichen; Shi, Fanxing; Zhu, Junyu; Yuan, Yi (Frontiers in Immunology, 2025)
Glioblastoma multiforme (GBM) is a common primary malignant brain tumor in adults, characterized by a high rate of recurrence and mortality. The median overall survival is less than 2 years with the current standard therapy. As immunotherapy has begun to show promising results in solid tumors such as non-small cell lung cancer and melanoma in recent years, immnunotherapy for patients with glioblastoma is also in full swing, which is mainly consisted of immune checkpoint inhibitors, cancer vaccines, chimeric antigen receptor T-cell and oncolytic viral therapy. However, the application of immunotherapy in glioblastoma is severely hampered by cognitive impairment of intracerebral lymphatic system, the existence of blood-brain barrier, highly immunosuppressive tumor microenvironment and GBM’s intrinsic features, including low tumor mutation burden and high heterogeneity. This review systematically evaluates recently published clinical trial outcomes of GBM immunotherapy, critically analyses both the progress and limitations of these trials, thoroughly examines current barriers to effective immunotherapy, and highlights promising preclinical studies that may guide future therapeutic development.